THE EFFECT OF SPIRITUAL EDUCATION ON STATE AND SOCIETY ADMINISTRATION - Akhmedova O’gilkhan Namozovna (Zeta Repository, 2023)
In this article, it is revealed that in the process of management of modern society, it is necessary to fully demonstrate certain spiritual, social, scientific and other opportunities for the all-round development of creative personnel. A socio-philosophical analysis has been made that the mature leader and his spiritual characteristics should be compatible with modernization and integration in the current period. This is based on the fact that moral qualities in people, no matter how beautiful or ugly they are, are manifested only in social activities.